2017
DOI: 10.21037/cdt.2016.08.06
|View full text |Cite
|
Sign up to set email alerts
|

Infarct related artery only versus complete revascularization in ST-segment elevation myocardial infarction and multi vessel disease: a meta-analysis

Abstract: (ACCF/AHA) focused update on primary percutaneous coronary intervention (PCI) for patients with STsegment elevation myocardial infarction (STEMI) only gives a class II b (weak) indication for non-infarct artery intervention at the time of primary PCI. Recent randomized controlled trials, however, suggest strong evidence supporting complete revascularization.Methods: A systematic search was conducted in PUBMED, MEDLINE, EMBASE and Cochrane central register for randomized controlled trials comparing complete ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 27 publications
(40 reference statements)
0
6
0
1
Order By: Relevance
“…Recent metaanalysis emphasizes performing single setting complete revascularization in acute coronary syndrome. 24,25 As was seen in our patient population, both genders garnered better outcomes of mortality, MACEs and overall complications when complete revascularization was performed, although our patient population was not a STEMI cohort but did include non-STEMI and acute coronary syndrome patients. Traditionally CABG has been demonstrated to have improved long term benefits over PCI in this CHIP population, although only in coronary artery bypass grafting (CABG) eligible patients.…”
Section: Discussionmentioning
confidence: 79%
“…Recent metaanalysis emphasizes performing single setting complete revascularization in acute coronary syndrome. 24,25 As was seen in our patient population, both genders garnered better outcomes of mortality, MACEs and overall complications when complete revascularization was performed, although our patient population was not a STEMI cohort but did include non-STEMI and acute coronary syndrome patients. Traditionally CABG has been demonstrated to have improved long term benefits over PCI in this CHIP population, although only in coronary artery bypass grafting (CABG) eligible patients.…”
Section: Discussionmentioning
confidence: 79%
“…Both females and males, had better outcomes in terms of mortality, MACE and overall complications when complete revascularization was performed. [21][22][23][24] In addition, 90-day follow-up data from the PROTECT II trial showed a significant decrease in major adverse 30-day survival rates Secondary outcomes such as major adverse cardiac events, dialysis requirement, bleeding within 72 hr, blood transfusion, dysrhythmia were similar in both cohorts. 25 Complete revascularization is often achieved with CABG surgery and has been shown to be associated with long-term mortality benefits.…”
Section: Discussionmentioning
confidence: 99%
“…gold standard treatment, its outcome may not be much different from other treatment modalities such as stents with percutaneous coronary intervention (PCI) while all treatment modalities are associated with a considerable risk of mortality and recurrence of MI (7,8).…”
Section: Key Pointmentioning
confidence: 99%